Theoretical and experimental exploration into the fluid structure coupling dynamic behaviors towards water-lubricated bearing with axial asymmetric grooves. (1st April 2022) - Xie, Zhongliang; Wang, Xuerui; Zhu, Weidong
Highlights: The revised FSI models with cavitation and turbulent effects are proposed. Effects of grooves types and locations towards the FSI behaviors are explored. The mechanism of the separation effects of the grooves coupled with the rotation effects are revealed. Stimulations are consistent with the literature and experimental data, indicating the correctness of the model. Abstract: The work studies the fluid structure interaction (FSI) dynamic behaviors of water-lubricated bearing with axial asymmetric grooves. Revised FSI models with consideration of cavitation and turbulent effects are put forward. Stimulations are consistent with the literature and experimental data, indicating the correctness of the model. Effects of groove types, locations in ascending/descending zones towards the dynamic behaviors are explored in details systematically. The separation effects of the local asymmetric grooves coupled with the rotation effects further enhances the hydrodynamic effects, which will directly lead to the growth of maximum pressure values and the load carrying capacity (LCC). Research fruits have important guiding significances for the optimization design of the surface microstructures and micro-textures, especially the design of axial asymmetric grooves for such bearings.